Thermal, Morphological and Rheological Study of Polytrimethylene Terephthalate/ Thermotropic Liquid Crystalline Polymer Binary Blend - Maleknia, Laleh; Nazockdast, Hossein; Saeed Rashidi, Aboo; Esmaeel Yazdanshenas, Mohamad (Asian Journal of Chemistry, 2010)
The miscibility of thermotropic liquid crystalline polymer (TLCP) and polytrimethylene terephthalate (PTT) blends was investigated with thermal, morphological and melt viscoelastic analyses. The blend samples containing 5, 10 and 15 % of TLCP were prepared by both in an internal mixture and a modular twin screw extruder. The results obtain from DSC showed the heat of fusion and heat of crystallization of the blend samples was found to be slightly lower than those predicted from additive rule and indicated small compatibility between PTT and TLCP phases. Cryogenically fractured surface of the blend samples examined by SEM. The SEM showed a matrix-dispersed type morphology in which TLCP phase was uniformly dispersed in polymer matrix. The shear viscosity as well as melt elasticity of the TLCP were matched quarter than PTT matrix. The melt flow behaviour of TLCP showed an appreciable viscosity up turn and a non-terminal storage modulus (G') at low shear rate range while PTT showed a sudoplastic type flow behaviour.